Large-Scale Synthesis and Applications of Hafnium-Tantalum Carbides; Advanced Functional Materials; Vol. 32, iss. 38 - Kvashnin A. G. Alexander; Nikitin D. S. Dmitry Sergeevich; Shanenkov I. I. Ivan Igorevich; Chepkasov I. V. Ilya; Kvashnina Yu. A. Yulia; Nassyrbayev (Nasyrbaev) A. Artur; Sivkov A. A. Aleksandr Anatolyevich; Bolatova Zh. S. Zhanar Sanatovna; Pak A. Ya. Aleksandr Yakovlevich (2022, 2022)
Title screen